Economic policy uncertainty, financial reporting quality, and accounting enforcement: International evidence - Catalin Robert Mos (Finance, Accounting and Business Analysis)
Purpose: Given recent developments around the world, the purpose of this article is to explore the association between financial reporting quality and economic policy uncertainty. Additionally, we investigated whether accounting enforcement acts as a mediating factor between the two.